Título Padrão - Oliveira Fortaleza, Matheus; Maria Lemos Girão, Magalline; Franklin Junior, Wilson; Pinto de Lima, Jadson; de Almeida Rocha-Barreira, Cristina (Arquivos de Ciências do Mar, 2020)
The ghost crab Ocypode quadrata is commonly found in the middle and supralittoral areas of sandy beaches along the Brazilian coast. It is a known and important species in the ecology of beaches, which inhabit semi-permanent burrows excavated, maintained, and protected by them. This study evaluated the density and diameter of O. quadrata burrows, considering three lunar cycles in a Conservation Unit on the coast of Ceará state, Northeastern Brazil. Quarterly samplings were performed between 2014 and 2015 during the early morning in the four phases of the moon over three lunar cycles. The tidal range (high tide and low tide) and nocturnal luminosity were used to evaluate the effects of the lunar phases on crab behavior. The lunar cycles influence the activity of the O. quadrata, varying the density, diameter, and distribution of the burrows along the beach, due to changes in the tide conditions and nocturnal luminosity. The construction of burrows by the crabs was higher in the moons that provided more bright nights. Keywords: ghost crab, burrows, Canto Verde beach, phases of the moon.